Tharu Community Conscience and Perception on Sickle Cell Anemia - Pokharel, Saroj; Adhikari, Bhawani Shankar; Chaudhary, Asha Ram (THE ACADEMIA, 2026)
Sickle cell disease (SCD) is a genetic blood condition which is very common in the Terai region of Nepal among the Tharu people. The study scrutinizes about the social construction of SCD, highlighting how cultural aspects, healthcare accessibility and the extended societal views interaction affecting managerial and awareness sector in Tharu community. The study aims at examining the views of tharu community regarding SCD long with its effects. It particularly emphasizes people experienced with the illness and their awareness. The study presents the growth of awareness of SCD among people in the Tharu community. Traditional healers function seems to be changed as people tends to follow healthcare practices. Government still fail to assist the gaps in accessibility and education. One of the contributing factor for SCD prevalence is the cultural norms surrounding marriage which needs to be addressed. Focusing on intervention programs and comprehensive education can improve health outcomes. This study acknowledges insufficiency of people in reference to realization and awareness of SCD in Kailali, Nepal. Despite awareness, strategic governance is hindered by illiteracy and fallacy. In order to confront the genetic traits and sociocultural dimensions of SCD, the study focuses on the requirement of helping network and targeted educational program.